TOMI digital en el proceso de Aprendizaje de Biología Vegetal con los estudiantes de tercer semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Garzón Orejuela, Cintia Nayeli (2025)
This research focused on the Pedagogy program in Experimental Sciences, specifically in Chemistry and Biology, where it was identified that traditional teaching methods generated little interest in meaningful learning. To address this issue, the implementation of a didactic guide titled "Plant Kingdom" was proposed, aiming to improve students' understanding of the characteristics, definitions, parts, and functions of higher plants. The methodology employed was Problem-Based Learning (PBL) and the TOMI Digital tool to promote interaction between teachers and students. Using a quantitative approach and non-experimental, field, bibliographic design with a descriptive level, the study included a survey applied to 27 third-semester students. The results indicated that the students considered the didactic guide excellent, successfully awakening their interest in the subject. It suggested integrating digital technologies and interactive methods could transform the educational process. In conclusion, applying this guide favored meaningful learning and stimulated student motivation to actively engage in their academic development. The use of digital resources and innovative pedagogical approaches is deemed essential for revitalizing interest in Plant Biology. It is recommended that didactic guides be utilized and expanded and designed to incorporate more interactive resources and activities, thus preparing future educators to face learning challenges